Quadruple Witching Days and Abnormal Returns Analysis in The Indonesian Stock Market - Zulfikar, Fahmi; Endri, Endri (Green Publisher Indonesia, 2024)
The aim of this research is to analyze the Quadruple Witching Days phenomenon and its impact on abnormal returns on the Indonesian stock market. This phenomenon has attracted the attention of many investors and academics, because it is believed to be able to significantly influence stock price movements. It is hoped that the results of this research can provide an in-depth understanding of the influence of Quadruple Witching Days on the Indonesian capital market. Associative descriptive research tests the influence of Quadruple Witching Days. Using secondary data and library methods in the LQ45 and SRI-KEHATI stock indices listed on the Indonesia Stock Exchange for the period 2010 to 2022 with daily and weekly data. The hypothesis test that will be used in this research is the Paired Sample t - Test and the non-parametric Mann-Withney test. There are differences in abnormal returns before and after the Quadruple Witching Days event on the LQ45 stock index. There is no difference in abnormal returns before and after the Quadruple Witching Days event on the SRI-KEHATI stock index. High Vigilance, Quick Selling or Buying, Portfolio Diversification as a consideration for taking profits for investors LQ45, Long Term Investment Approach, Portfolio Stabilization may be more suitable with investment strategies because there is no significant difference in abnormal returns, investors in SRI-KEHATI.